Interrelationships Between Quantitative Geomorphic Characteristics of the Drainage Basins in Sub-Humid to Humid Environment of Rajasthan - Singh, S; Ghose, B (Annals of Arid Zone, 2016)
By developing mathematical drainage basin models, the interrelationships between different quantitative geomorphic characteristics of 15 small agricultural drainage basins of Banas catchment have been discussed. The results of this study have shown that the quantitative analysis of the drainage basins characteristics and their interrelationships with each other will substantially contribute to the estimation of water and sediment yield of the catchment.